The diagnosis and treatment of primary dysmenorrhea - Obuchowska, Karolina; Obuchowska, Aleksandra; Standyło, Arkadiusz; Gorczyca, Kamila; Wójcik-Grudzień, Justyna; Ozga-Stachurska, Alicja; Pawłowska, Paulina; Rozenbajgier, Martyna; Żelazny, Przemysław; Filipczak, Joanna; Kimber-Trojnar, Żaneta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2022)
Primary dysmenorrhea is defined as pain in the pelvic area that occurs for no specific reason during menstrual cycle. Dysmenorrhea occurs in 50% to 90% of adolescent girls and women of reproductive age which makes it one of the most common causes of pelvic pain in women. The mechanism of this condition is overproduction of prostaglandins by the endometrium, causing uterine hypercontractility, thereby leading to uterine muscle ischemia, hypoxia and pain. Dysmenorrhea significantly reduces the quality of women life, often making it impossible to perform daily activities and, in addition, it may cause a mental stress that makes both professional and school life difficult. Despite this, females often consider these symptoms as a normal part of their menstrual cycle, which makes this disease underrated and untreated. Dysmenorrhea can be treated in a various ways such as non-pharmacological, pharmacological and surgical. However, women with a typical history of primary dysmenorrhea can commence empirical therapy without any additional tests. Hormonal contraception and nonsteroidal antiinflammatory drugs have proved to be effective in this treatment. However, if conventional treatment is contraindicated, alternative treatments such as topical heat, lifestyle modification, transcutaneous electrical nerve stimulation, dietary supplements, acupuncture, and acupressure may be used. Surgical treatment is possible, but it is used rarely and only in severe cases of treatment-resistant dysmenorrhea. However, it should be emphasized how important it is to exclude secondary causes of dysmenorrhea.